Frenzy [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Shaffer, Anthony, 1926-2001; Finch, Jon, 1941-2012; McCowen, Alec; Foster, Barry, 1931-2002; Whitelaw, Billie, 1932-2014; La Bern, Arthur J. (Alfred Hitchcock collection., 2005)
In modern-day London, a sex criminal known as the Necktie Murderer has the police on alert; and in typical Hitchcock fashion, their trail is leading to an innocent man who must now elude the law and prove his innocence by finding the real murderer.